CHILD DOMESTIC VIOLENCE IN THE SOCIETY: IMPLICATION FOR COUNSELLING - ADEKUNLE, Abubakar, S.; AMINU, Umaru; MONDAY, Gaiyas (Journal of Professional Counselling, 2025)
This paper examines child domestic violence in the society. It is no longer news that a lot of children had experienced and still experiencing child domestic violence or abuse in one form or the other. Forms of domestic violence which include physical abuse, sexual abuse, verbal abuse or emotional abuse and psychological abuse. The article views the different causes of child domestic violence like social stress, intergenerational transmission of violence, social isolation and community involvement and family structure. Whereas, post-traumatic stress disorder (PTSD), result in death, low self-esteem, stress disorders, anxiety, depression, sexual transmitted infection, unwanted pregnancy, and educational difficulty are all effects of child domestic violence. Preventive measures are also taken to reduce the rate of child domestic violent. The related theory used was reframing theory, which simply means changing the interpretation of a behaviour or situation to alter its perceived meaning. Conclusively, the counsellors, educational psychologists and other relevant agencies carry out constant workshop to sensitize parents, guardians, and teachers. So as to be aware of the implication of child domestic violence and promptly report any related abuse to the appropriate authority.